PEMANFAATAN PATI BIJI DURIAN (Durio zibethinus L.) SEBAGAI EDIBLE COATING DALAM MEMPERTAHANKAN MUTU ANGGUR MERAH (Vitis vinifera L.) - Cornelia, Melanie; Tandoko, Rika (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2017)
ABSTRACT.   Red grape fruit (Vitis vinifera L.) was one of non-climacteric fruit that easily damaged. Changes that occurred in damaged grape was becoming wrinkle and wither, browning, and fruit flesh softening. Durian seed was one of food waste that contains high enough starch so it could be used as a basic ingredient for making edible coating. The objectives of this research were to make edible film from durian seed starch with different concentration of durian seed starch (2%, 4%, 6%, 8%, and 10%) and glycerol 3% addition.  Edible films' physical and mechanical characteristics such as tensile strength, elongation, and water vapor transmission rate were analyzed.  The best edible film will be used for coating of red grapes. Finally, doing analyzing the effect of edible coating towards quality of red grapes that were stored at room and refrigeration temperature. Physical and chemical characteristic of red grapes such as skin puncture, weight loss, pH, total titratable acid, and total dissolved solid were analyzed during storage. The results showed that edible film with the higher concentration of durian seed starch had higher tensile strength, elongation, and thickness, but had lower water vapor transmission rate. The best edible film was an edible film with 6% durian seed starch and 3% glycerol. The results also showed that application of the edible coating on red grapes could maintain the quality of grape during storage, prolonged the shelf life up to 18 days at room temperature and up to 30 days at refrigeration temperature.Keywords: durian seed, edible coating, physicochemical quality, red grape, shelf life